2006
DOI: 10.1074/jbc.m606263200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Growth of Lactobacillus plantarum WCFS1 on a Complex Medium Using a Genome-scale Metabolic Model

Abstract: A genome-scale metabolic model of the lactic acid bacterium Lactobacillus plantarum WCFS1 was constructed based on genomic content and experimental data. The complete model includes 721 genes, 643 reactions, and 531 metabolites. Different stoichiometric modeling techniques were used for interpretation of complex fermentation data, as L. plantarum is adapted to nutrient-rich environments and only grows in media supplemented with vitamins and amino acids. (i) Based on experimental input and output fluxes, maxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
271
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(305 citation statements)
references
References 50 publications
13
271
1
Order By: Relevance
“…Comparing this to growth yields that he had corrected for growth rate independent maintenance, he found that the experimental growth yields were far below the theoretical ones [54]. Perhaps not surprisingly therefore, cases have already been reported where predictions by FBA concerning the flux pattern were not realistic [53,55].…”
Section: Maximum Growth Yield or Atp Is Not A Good Paradigmmentioning
confidence: 96%
“…Comparing this to growth yields that he had corrected for growth rate independent maintenance, he found that the experimental growth yields were far below the theoretical ones [54]. Perhaps not surprisingly therefore, cases have already been reported where predictions by FBA concerning the flux pattern were not realistic [53,55].…”
Section: Maximum Growth Yield or Atp Is Not A Good Paradigmmentioning
confidence: 96%
“…Construction of host-microbe models We retrieved 11 manually constructed and validated reconstructions of human gut microbes 13,[43][44][45][46][47][48][49][50] and an extensive, highquality reconstruction of human metabolism.…”
Section: Methodsmentioning
confidence: 99%
“…Flux ranges in general fell into four categories: (i) inflexible fluxes (range of ϳ0), (ii) fluxes with bounded (but not zero) flexibility, (iii) infinitely flexible fluxes, and (iv) reactions that cannot carry flux (the last were excluded from the rest of the FVA). Infinitely flexible fluxes arise in metabolic models through the cycling of zero-sum loops, which generally do not reflect biologically significant states (38). Figure 7c displays statistics for how many reactions display fluxes with these different ranges in each functional category, for the M9 and M13 (month 8 and month 21) in silico states, when maximal biomass production was enforced.…”
Section: Integration Of Gene Expression Into the Metabolic Networkmentioning
confidence: 99%